Investigating the Impact of Renewable Energy Investment Announcements on Stock Returns of Borsa Istanbul Energy Companies - Kandir, Serkan Yilmaz; Mermer, Gozde Elbir (International Journal of Energy Economics and Policy, 2024)
Aim of this study is to investigate whether renewable energy investment announcements impact the stock returns of 10 energy companies listed in Borsa Istanbul. Event study method is employed to analyze 25 renewable energy investment announcements during April 2015 and December 2023 period. Announcement date is defined as the event day and the 5 day period before and after the event day is selected as the event window. The length of the pre-event window in the timeline is chosen as 244 days. The total length of the period studied in the study is 250 days. The result of the study reveals that the renewable energy investment announcements of the energy companies listed in Borsa Istanbul seem to have no significant impact on the stock returns. Thus, Borsa Istanbul appears to be semi-strongly efficient.